An evaluation of coordination relationships during earthquake emergency rescue using entropy theory - Huang Rong; Liang Xuedong; Zeng Guizhi; Ye Yulin; Wang Da (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
Emergency rescue after an earthquake is complex work which requires the participation of relief and social organizations. Studying earthquake emergency coordination efficiency can not only help rescue organizations to define their own rescue missions, but also strengthens inter-organizational communication and collaboration tasks, improves the efficiency of emergency rescue, and reduces loss. In this paper, collaborative entropy is introduced to study earthquake emergency rescue operations. To study the emergency rescue coordination relationship, collaborative matrices and collaborative entropy functions are established between emergency relief work and relief organizations, and the collaborative efficiency of the emergency rescue elements is determined based on this entropy function. Finally, the Lushan earthquake is used as an example to evaluate earthquake emergency rescue coordination efficiency.